An investigation into the effect of ruminal and post-ruminal administration of casein on milk yield and composition : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Animal Science at Massey University - Chandler, Neville James (Massey University, 1971)
The metabolism of protein in the digestive tract of the ruminant and its subsequent effect on production involves many reactions. In the rumen, proteolysis occurs, forming amino acids, volatile fatty acids and ammonia. The rumen micro-organisms can utilise the products of protein breakdown for growth. Undigested feed protein-N and microbial-N pass to the lower digestive tract where digestion and absorption of amino acids occurs. Once absorbed, the amino acids may be metabolised at the liver, where the end products vary according to the glucogenic or ketogenic nature of the amino acids. The amino acids may also be utilised in protein production. The following review encompasses the fate of dietary protein, and its subsequent effect on dairy production.
Keywords: Rumen microbiology; Milk yield; Milk production; Amino acids; Protein production